IMMUNOPATHOGENETIC ASPECTS OF ECTOPIC FETAL ORIGIN AND IMPROVEMENT OF ITS PREVENTION - Saidjalilova D. D. M. n proff; Tuktamysheva Nargiz Orifjonovna (Scholar Express Journals, 2023)
In this article, thoughts are expressed about ectopic pregnancy, its causes, consequences, prevention and effectiveness of treatment.
Keywords: Ectopic; pregnancy; ectopic fetus